The Role of DACUM Method in Designing Training Programs in Security Institutions: An Empirical Research in Iraqi National Security Services - Ameer Abbas*, Mustafa; Dawood Salman, Mazin (Journal of Economics and Administrative Sciences, 2024)
The current research has aimed to achieve a set of main objectives, which include diagnosing training needs based on their dimensions (identifying training needs, training planning, training content, training implementation, training evaluation, and feedback). This research focused on the necessary factors required to apply Developing Curriculum (DACUM) method in designing training programs according to the requirements and needs of security institutions in Iraq. The researcher assumed that there is a significant effect of DACUM method with its five dimensions (analysis, design, development, implementation, and evaluation) on designing the training program with its six dimensions (identifying training needs, training planning, training content, training implementation, training evaluation, and feedback). This method is considered a cost-effective approach compared to other methodologies. It aims to identifying training needs, improving performance, and developing work processes. This research adopted a descriptive statistic technique, relying on a questionnaire as the major instrument for data collection. The research population was 224 employees, while the sample size was 142 employees, according to De Morgan’s Table for samples. The researcher used several statistical methods, that included Cronbach’s alpha, normal distribution test, Pearson correlation coefficient, and simple linear regression. The statistical software used for analysis was (SPSS V26 and Excel). The research showed several vital findings represented statistically significant; the variable (DACUM) method and its dimensions directly affect the design of the training program in security institutions.